The human amygdala in social judgment - Adolphs, Ralph; Tranel, Daniel; Damasio, Antonio R. (Nature (London), 1998)
Studies in animals have implicated the amygdala in emotional 1 , 2 , 3 , and social 4 , 5 , 6 , behaviours, especially those related to fear and aggression. Although lesion 7 , 8 , 9 , 10 , and functional imaging 11 , 12 , 13 , 14 , studies in humans have demonstrated the amygdala's participation in recognizing emotional facial expressions, its role in human social behaviour has remained unclear. We report here our investigation into the hypothesis that the human amygdala is required for accurate social judgments of other individuals on the basis of their facial appearance. We asked three subjects with complete bilateral amygdala damage to judge faces of unfamiliar people with respect to two attributes important in real-life social encounters: approachability and trustworthiness. All three subjects judged unfamiliar individuals to be more approachable and more trustworthy than did control subjects. The impairment was most striking for faces to which normal subjects assign the most negative ratings: unapproachable and untrustworthy looking individuals. Additional investigations revealed that the impairment does not extend to judging verbal descriptions of people. The amygdala appears to be an important component of the neural systems that help retrieve socially relevant knowledge on the basis of facial appearance.